DEVELOPMENT OF A SPECTROPHOTOMETRIC METHOD FOR THE ASSAY OF BROMHEXINE HYDROCHLORIDE IN ITS PURE FORM AND IN ITS PHARMACEUTICAL PREPARATIONS USING DIAZOTIZATION - COUPLING REACTION (Jurnal Teknologi (Sciences & Engineering), 2025)
A simple, rapid, and accurate spectrophotometric method has been developed for determining bromhexine hydrochloride (BROH) in its pure form and pharmaceutical formulations. The method is based on the reaction of diazotized bromhexine hydrochloride (DBROH) with the organic reagent 4-chlororesorcinol (4CRC) in the presence of a sodium hydroxide basic medium. This reaction produces a stable, water-soluble orange-colored azo dye, which exhibits maximum spectral absorption at a wavelength of 455 nm.The method demonstrated high sensitivity, with a molar absorptivity of 43,548 L/mol•cm. The limit of detection (LOD) and limit of quantification (LOQ) were determined to be 0.322 µg/mL and 1.073 µg/mL, respectively. The proposed method was successfully applied to the analysis of bromhexine hydrochloride in pharmaceutical preparations, including syrups and tablets, showcasing its efficacy and reliability.